Enhancing thermal efficiency and durability of sintered clay bricks through incorporation of polymeric waste materials - Erdogmus, Ertugrul; Sutcu, Mucahit; Gencel, Osman; Kazmi, Syed Minhaj Saleem; Munir, Muhammad Junaid; Muñoz Velasco, Pedro; Ozbakkaloglu, Togay (Journal of Cleaner Production, 2024)
This pioneering study investigates the use of expanded polystyrene (EPS) and waste rubber tyre powder (WRTP) in sintered clay bricks for eco-friendly and cleaner buildings. Different ratios of EPS and WRTP were mixed with clay and sintered at 1000 °C. Advanced material characterization techniques were used to evaluate the materials, and physical, mechanical, and durability tests were performed on the bricks. The findings show that higher doses of EPS and WRTP increased the bricks' thermal efficiency and reduced their weight. Brick specimens with 0.5% EPS dosage met the weathering resistance requirements, and those with 0.5% EPS dosage and 5% WRTP dosage met the minimum compressive strength standards. The study offers valuable insights into the potential applications of EPS and WRTP in producing clean and sustainable polymer waste bricks to improve brick performance and efficient waste management in the construction industry.
Keywords: thermal efficiency; polymeric waste materials; cleaner production; Scopus